Human Security dan Islam: Studi Kasus Kematian Jamal Ahmad Khasoggi - Willi Ashadi (Dauliyah Journal of Islamic and International Affairs, 2019)
This study discusses the concepts of Human Security and Islam with a case study of the death of Jamal Ahmad Khasoggi in October 2018, a senior journalist from Saudi Arabia. This event became an international spotlight and had an impact on the three countries involved, Saudi Arabia, Turkey and America which resulted in their relationship being in harmony. What are the theories and concepts of Human Security at the global level and what are the red threads of the concept of human security in Islam and the implementation of the Perspective of Human Security and Islam in the case of Jamal Ahmad Khashoggi. This research uses research literature method to collect secondary data. This research uses qualitative descriptive technique and analysis to obtain a complete picture of the answer to the problem under study. The results of the study show that the concepts of Human Security and Islam have a common goal of upholding the right to life and humanity. The death e of Jamal Ahmad Khasoggi violated the concept of Human Security, Islam and the universal value of humanity.